(untitled) (Journal of Faculty of Education, 2021)
The paper aims to reveal the value of poetry literature included in history books in order to show the literary value of these books. The significance of this paper lies on that it draws the attention of researchers to look for Arabic literature in various sources beyond the specialized booksin the field such as history books, biographies and translations. The paper includes an introduction of the Imam Ibn -eljawzi and his books “Almuntadham” in the history of kings and nations which contains more than two hundreds poems, more than nine hundreds poetry pieces in addition to verses, “Rajaz” and other types of poetry It also includes a study of the poetry of Ibn-eljawzi not mentioned the above-mentioned book but included in the books of other poets whoare mostly his friends The researcher adopts the descriptive analytical methodology. The most important findings include;: history books contain a great literary value because they contain in many instances selected texts which blend the narration of historical events and biographies. The study also revealed that the book “Almuntadham”. includes many poetry pieces not included in the books written by the poets who said them. The researcher recommends conducting literary studies on Arabic literature and related Islamic books which are not necessarily pure literary books.